Tafsir QS. An-Nisa Verse 34: Leadership Perspective and Gender Justice in the Household - Daud Pisba, Syauqi Musfirah; Rulaila, Rulaila; Massyahid, Ridwan; Luthfi, Atabik; Muhayar, Marhadi (Journal of Islamic Education Students (JIES), 2025)
Classical interpretations of QS. An-Nisa’ 34 often reinforce patriarchal bias and construct gender relations in hierarchical terms. This study re-examines the verse through the reformist perspective of Rasyid Ridha in Tafsir al-Manar to offer a more just and contextual reading. Employing a library-based qualitative design with a descriptive-analytical approach enriched by content analysis and contextual-historical interpretation, the study uses Tafsir al-Manar as the primary source supported by academically relevant secondary literature. The findings reveal that Ridha understands qawwamah not as a justification for male domination, but as a moral mandate of leadership grounded in justice, compassion, and family responsibility. He asserts that role differences between men and women do not indicate superiority but reflect proportional functional division. These findings highlight Ridha’s significant contribution to developing a more humanistic and egalitarian contextual interpretation relevant to contemporary discussions on gender justice in Islam.